Evaluation of Aqueous and Ethanolic Extracts for the Green Synthesis of Zinc Oxide Nanoparticles from Tradescantia spathacea - Pedro Gerardo Trejo-Flores; Yazmin Sánchez-Roque; Heber Vilchis-Bravo; Yolanda del Carmen Pérez-Luna; Paulina Elizabeth Velázquez-Jiménez; Francisco Ramírez-González; Karen Magaly Soto Martínez; Pascual López de Paz; Sergio Saldaña-Trinidad; Roberto Berrones-Hernández (Nanomaterials)
In this work, we report a green synthesis of zinc oxide (ZnO) nanoparticles using aqueous and ethanolic extracts of Tradescantia spathacea (purple maguey) as bioreducing and stabilizing agents, which are plant extracts not previously employed for metal oxide nanoparticle synthesis. This method provides an efficient, eco-friendly, and reproducible route to obtain ZnO nanoparticles, while minimizing environmental impact compared to conventional chemical approaches. The extracts were prepared following a standardized protocol, and their phytochemical profiles, including total phenolics, flavonoids, and antioxidant capacity, were quantified via UV-Vis spectroscopy to confirm their reducing potential. ZnO nanoparticles were synthesized using zinc acetate dihydrate as a precursor, with variations in pH and precursor concentration in both aqueous and ethanolic media. UV-Vis spectroscopy confirmed nanoparticle formation, while X-ray diffraction (XRD) revealed a hexagonal wurtzite structure with preferential (101) orientation and lattice parameters a = b = 3.244 Å, c = 5.197 Å. Scanning electron microscopy (SEM) showed agglomerated morphologies, and Fourier transform infrared spectroscopy (FTIR) confirmed the presence of phytochemicals such as quercetin, kaempferol, saponins, and terpenes, along with Zn–O bonding, indicating surface functionalization. Zeta potential measurements showed improved dispersion under alkaline conditions, particularly with ethanolic extracts. This study presents a sustainable synthesis strategy with tunable parameters, highlighting the critical influence of precursor concentration and solvent environment on ZnO nanoparticle formation. Notably, aqueous extracts promote ZnO synthesis at low precursor concentrations, while alkaline conditions are essential when using ethanolic extracts. Compared to other green synthesis methods, this strategy offers control and reproducibility and employs a non-toxic, underexplored plant source rich in phytochemicals, potentially enhancing the crystallinity, surface functionality, and application potential of the resulting ZnO nanoparticles. These materials show promise for applications in photocatalysis, in antimicrobial coatings, in UV-blocking formulations, and as functional additives in optoelectronic and environmental remediation technologies.